Assessment of propeller 1P loads predictions. (1st January 2012) - Ortun, Biel; Boisard, Ronan; Gonzalez-Martino, Ignacio
A comparison of the airloads on a propeller in incidence is done between experimental wind tunnel data, lifting-line results and unsteady Reynolds-averaged Navier-Stokes (URANS) calculations. The experimental behaviour of the high-speed, scale-model, APIAN propeller in the transonic S1MA wind tunnel at various angles of attack at Mach 0.20 and Mach 0.70 is successfully predicted by ONERA's computational fluid dynamics (CFD) code elsA. An assessment is done on the ability of the two numerical methods, namely lifting-line and URANS, to calculate propeller in-plane airloads. The importance of wake capture for accurate predictions is underlined and illustrated through comparisons on grid effects. Special emphasis is put on the airloads induced by the propeller on the spinner, which may amount up to 56% of the airloads on the propeller itself. Last, it is argued that neglecting these airloads biased the corrections done on the wind tunnel balance measurements.